GAMBARAN PENGETAHUAN REMAJA PUTRI TENTANG SADARI DAN PRAKTIK PEMERIKSAAN PAYUDARA SENDIRI - Anugrah Dian Wardhani; Lintang Dian Saraswati; Mateus Sakundarno Adi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
This research is motivated because the researchers wanted to know the practice of BSE inspection in accordance with his knowledge and aims to describe the level of knowledge on young girls about BSE and practice breast self-examination in adolescent girls. The unit of analysis in this study is an epidemiological specialization 7th semester student of the Faculty of Public Health Diponegoro University, Semarang, which amounted to 65 student. Therefore the population is under 100, then set the entire population were sampled, so that the sampling technique used is total sampling. However, in practice the number of samples analyzed as many as 52 people.The study concluded thatrespondents have a level of knowledge about BSE belong to the upper middle, with an average of 68.46% in the level of knowledge about BSE category is quite sure. The results showed that most respondents had a breast exam intensity of belonging to the upper middle, with an average of 51.28% is in the category often practice breast examination alone.